1985
DOI: 10.1302/0301-620x.67b3.3997942
|View full text |Cite
|
Sign up to set email alerts
|

Methods of fixation of olecranon fractures. An experimental mechanical study

Abstract: This study was designed to compare the rigidity of the more commonly used techniques of internal fIxation of fractures of the olecranon. Cadaveric elbow joints were mounted in a jig and confrolled osteotomies performed to simulate transverse, oblique or comminuted fractures. Five techniques of internal fixation were tested by measuring movement at the fracture site after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
73
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 3 publications
1
73
0
5
Order By: Relevance
“…Since 1883, there have been many reports on plate fixation of comminuted olecranon fractures, with variable results, as noted by Hak and Golladay in a review article 4 . Plate fixation is the current gold standard for the treatment of these fractures [4][5][6][7] . Contoured plating of the olecranon, in which the proximal end of the plate is wrapped around the tip of the olecranon, leads to good results when used for the treatment of oblique fractures [7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Since 1883, there have been many reports on plate fixation of comminuted olecranon fractures, with variable results, as noted by Hak and Golladay in a review article 4 . Plate fixation is the current gold standard for the treatment of these fractures [4][5][6][7] . Contoured plating of the olecranon, in which the proximal end of the plate is wrapped around the tip of the olecranon, leads to good results when used for the treatment of oblique fractures [7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, in our study we found that 82% of the removed metal work was fixed using two knots. We have found that having two knots will increase the chances of having metal work irritation whereas our patients with one-knot figure of eight formation did very well with a low percentage of metalwork removal.…”
Section: Discussionmentioning
confidence: 50%
“…Other authors have considered a plate to be too large an implant to be used, or only marginally better as a routine method of fixation for this kind of fracture (Fyfe et al 1985, Morrey 1995, Romero et al 2000. The AO principle of converting posterior tensile forces to articular compressive forces has been questioned in a mechanical test of 4 fixation techniques, which consisted of intramedullary and cortically fixed tension constructs, cancellous screw with and without a tension band (Hutchinson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A screw in conjunction with a tension band proved better fixation stability than the three other methods. In another mechanical study comparing 5 techniques of internal fixation of fractures of the olecranon, the tension band wiring with 2 tightening knots allowed minimal movement even at high loads (Fyfe et al 1985). Intramedullary cancellous screw fixation gave erratic results, even with the addition of a tension band.…”
Section: Discussionmentioning
confidence: 99%